The Aggregate and Residential Electricity Demand in Indonesia - Arnaz, Muhammad Zulfizal (Jurnal Ekonomi dan Pembangunan, 2018)
This paper presents an empirical analysis on electricity demand in Indonesia applying a double-log demand equation for aggregate and residential. This proposes static and dynamic models employing fixed effects and bias-corrected least square dummy variable estimators, respectively. Particular attention is paid to the effects of income, price, and the numbers of customers. The paper concludes that all regressors function as the determinants of electricity consumption. Price elasticities are inelastically negative as expected, and further, profound inelastic for residential. Meanwhile, income level and the number of customers are quite elastic for both models. In addition, interregional analysis reports the differential impacts of the price on energy consumption between Java Bali and non-Java Bali regions, showing less responsiveness of consumption to price in Java Bali. The long-run estimates give information on modest values of price elasticities for aggregate and residential. From an energy policy point of view, electricity price would be moderately effective in achieving efficiency and conservation programs. On the other hand, it gives an economic rationale for tariff adjustment and region-based tariff restructuring.